Natural food additives: Quo vadis? - Carocho, Márcio (2015)
In a time where the public is more aware and interested with what they eat, natural additives have been gaining interest both from the food industries and the consumers. Some studies show that consumers prefer food prepared with natural additives rather than chemical ones, due to health reasons. Although quite promising, natural additives still face some drawbacks and limitations as well as conflicting information. In this manuscript, the most important natural additives are overviewed, as well as their use, benefits and risks. The future of these molecules along with new types of additives are also summarized.